Analisis Pengaruh Kinerja Keuangan Terhadap Harga Saham Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia 2012-2014 - Nasution, Henry; , Zulfa Irawati., SE., MSi (2017)
This study aims to determine the effect of the partial significant between the dividend per share (DPS), Earning Per Share (EPS), Price Earning Ratio (PER), Debt to Equity Ratio (DER), the Current Ratio (CR), Net Profit Margin (NPM ), Return on Assets (ROA) on stock price (Common Price) in Manufacturing Companies Listed on the Stock Exchange and to know significant influence between the dividend per share (DPS), Earning Per Share (EPS), Price Earning Ratio (PER), debt Equity Ratio (DER), the Current Ratio (CR), Net Profit Margin (NPM), Return on Assets (ROA) together on stock price (Common Price) in Manufacturing Companies Listed on the Stock Exchange. The sampling technique used in this research is purposive sampling. The sample used in this study were 71 companies that have positive earnings from 2012 to 2014 year stock in order to obtain 71 x 3 = 213 samples.Based on these results the variable DPS, EPS and ROA have partial significant influence on stock price. Variable PER, DER, NPM and CR does not have a partial significant influence on stock price. F test analysis results showed variable DPS, EPS, PER, DER, CR, NPM and ROA jointly significant effect on stock price. And this shows that the model used is fit. The coefficient of determination with adjusted-R2 of 0.933. This means that 93.3% Stock Price variable variation can be explained by the variable DPS, EPS, PER, DER, CR, NPM and ROA while the remaining 6.7% is explained by other factors outside the model studied.